CLIMATE CHANGE AND ITS IMPACT ON AGRICULTURE, HEALTH, PSYCHOLOGY, HUMAN RESOURCE MANAGEMENT, AND FISHERY PRODUCT TECHNOLOGY: A MULTIDISCIPLINARY REVIEW - Hafiz Nurdiansyah; Liandra Khairunnisa; Dirhamsyah; Ahyani Ridhayani Lubis; Lucia Dewi Indrayani Manurung; Misnun; Nurhayati (PT. Radja Intercontinental Publishing, 2026)
Climate change is one of the greatest global challenges of the 21st century, impacting various aspects of human life. Rising global temperatures, shifting rainfall patterns, increasing extreme weather events, and rising sea levels have significantly impacted public health, psychological well-being, human resource management, and the fisheries industry. This article aims to examine the impacts of climate change in a multidisciplinary manner by integrating the latest research findings. The method used is a literature review through a review of scientific articles, international reports, and policy documents published in recent years. In the health sector, climate change increases the incidence of infectious diseases, heat-related illnesses, malnutrition, and environmental health disorders. From a psychological perspective, people experience increased stress, anxiety, depression, and eco-anxiety due to environmental uncertainty and loss of livelihoods. In human resource management, organizations are required to develop adaptation strategies through capacity building, occupational safety, organizational flexibility, and the development of green competencies. In the fisheries technology sector, climate change affects the quality of raw materials, increases the risk of post-harvest damage, and encourages innovation in processing, packaging, and more efficient cold chain technologies. A multidisciplinary approach is an important strategy in increasing community resilience to climate change.